Structure of a fully assembled γδ T-cell antigen receptor - Gully, BS; Ferreira Fernandes, J; Gunasinghe, SD; Vuong, MT; Lui, Y; Rice, MT; Rashleigh, L; Lay, C-S; Littler, DR; Sharma, S; Santos, AM; Venugopal, H; et al. (Springer Nature, 2024)
T cells in jawed vertebrates comprise two lineages, αβ T-cells and γδ T-cells, defined by the antigen receptors they express, i.e., αβ and γδ T-cell receptors (TCRs), respectively. The two lineages have different immunological roles, requiring γδ TCRs to recognize more structurally-diverse ligands1. Nevertheless, the receptors use shared CD3 subunits to initiate signaling. Whereas the structural organization of αβ TCRs is understood2,3, the architecture of γδ TCRs is unknown. Here, we used cryogenic electron microscopy to determine the structure of a fully-assembled, MR1-reactive human Vδ3Vγ8 TCR/CD3δγε2ζ2 complex bound by anti-CD3ε antibody Fab fragments4,5. The arrangement of CD3 subunits in γδ and αβ TCRs is conserved and, although the transmembrane α-helices of the TCR-γδ and -αβ subunits differ markedly in sequence, the packing of the eight transmembrane-helix bundles is similar6. However, in contrast to the apparently rigid αβ TCR2,3,6, the γδ TCR exhibits considerable conformational heterogeneity, owing to the ligand-binding TCR-γδ subunits being tethered to the CD3 subunits by their transmembrane regions only. Reducing this conformational heterogeneity by transferring the Vδ3Vγ8 TCR variable domains to an αβ TCR enhanced receptor signaling, suggesting that γδ TCR organization reflects a compromise between efficient signaling and the ability to engage structurally-diverse ligands. Our findings reveal the remarkable structural plasticity of the TCR on evolutionary timescales, and recast it as a highly versatile receptor capable of initiating signaling as either a rigid or flexible structure.